Artificial Intelligence Improving Student Learning Achievement - Hendrawan, Jajang Hendar; Anggraeni, Nurul Falah; Silah, Sumardianshah Bin; Anwar, Ali (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
This study examines the application of Artificial Intelligence (AI) in Education, mainly focusing on its impact on student achievement in the Pancasila and Citizenship Education Program at STKIP Pasundan. Students often face challenges when dealing with complex and abstract materials in civic Education. The research employs a quantitative approach, using random sampling and multiple linear regression analysis to assess the influence of AI. The findings reveal that ChatGPT is the most commonly used AI platform among students, valued for its user-friendly features and effective response capabilities. The analysis confirms that AI significantly affects student learning achievement, and its contribution is substantial compared to other influencing factors. Additionally, AI enhances student motivation, material absorption, and innovation in the learning process. In conclusion, AI positively and significantly impacts student achievement and can be integrated into educational practices to foster more innovative and practical learning in the digital era.